STUDY OF POSTOPERATIVE PSYCHIATRIC DISORDERS IN PATIENTS OF AMPUTATION - Kakade, Anupam; Padamwar, Mangesh; Mahakalkar, Chandrashekhar; Kamble, Ajonish; Nagdive, Amit (International Journal of Psychosocial Rehabilitation, 2020)
Amputation is emerging as a significant health strain on the health system, as well as on the families and community. Loss of limbs causes inability to sustain self and family which in many patients leads to different psychiatric disorders. The present research is therefore expected to investigate psychological comorbidity in amputated patients. Amputation of organ affects almost every aspect of a person’s life. Psychological elements are important coping factors for the impairment.The study was collaborated with Jawaharlal Nehru Medical College, Datta Meghe Institute of Medical Sciences, Sawangi (Meghe), Wardha, with Datta Meghe Medical College and Shalinitai Meghe Hospital and Research Centre, Hingna, Nagpur Maharashtra, in the Department of General Surgery in conjunction with Department Of Psychiatry. Over a period of 1 year 68 cases of amputation were studied whose surgery was done 6 months back. All participants were interviewed on a semi‑structured proforma of sociodemographic and amputation‑related parameters and assessed on psychiatric comorbidity using Mini‑International Neuropsychiatric Interview scale.All the patients were male and belonged to younger age group of 16–30 years 46 patients (67.64 %). Approximately, 66 patients had single‑limb amputation (97.05 %), predominantly right limb in 39 patients (57.35%). Road traffic accidents plays a major role in etiology of amputation followed by diabetic foot, peripheral vascular disease and electric burn injury. The most common psychiatric comorbidities in our sample were major depressive disorder in 48 patients (70.58%), suicidality in 08 patients (11.76%), and posttraumatic stress disorder (PTSD) in 12 patients (17.64%). PTSD was positively correlated with phantom sensation and phantom pain.A small number of amputees showed an troubling symptom of depression, suicidal thoughts and PTSD. Therefore, in order to control psychological comorbidity in amputees, liaison between surgical care providers and psychiatrists and psychologists must be established. We conclude that psychiatrist and psychologist play an important role in managing the cases of amputation in postoperative period along with surgeons.